Analisis SWOT Sebagai Strategi Pengembangan Hotel Muslim Kediri - Nur Hidayati; Lina Saptaria (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
Sharia hotels in Indonesia experience development and improvement from year to year. Evidenced by the emergence and establishment of several Islamic hotels including Muslim hotels in Kediri. The existence of a strategic place or location does not mean to make Muslim hotels avoid business competition. To increase guest visits at Muslim Hotels a strategy is needed to compete with other hotels in Kediri. Therefore, this research was conducted to discuss the SWOT analysis as a Muslim Hotel development strategy. This type of research is a qualitative study using SWOT analysis for Muslim Hotel strategy development strategies. The results obtained by the development of several Muslim Hotel strategies, including: (1) increasing product variety, setting affordable prices, increasing better service quality, (2) increasing the quality and quantity of more competent HR, increasing facilities, increasing capital, (3) maintaining product specific characteristics based on sharia economy, cooperating with Islamic boarding schools and government agencies, (4) making efforts to develop promotional strategies in all media to increase market share, increasing cooperation with various government and private agencies.